2015
DOI: 10.1002/ijc.29930
|View full text |Cite
|
Sign up to set email alerts
|

Complete reversal of muscle wasting in experimental cancer cachexia: Additive effects of activin type II receptor inhibition and β‐2 agonist

Abstract: Formoterol is a highly potent b 2 -adrenoceptor-selective agonist, which is a muscle growth promoter in many animal species. Myostatin/activin inhibition reverses skeletal muscle loss and prolongs survival of tumor-bearing animals. The aim of this investigation was to evaluate the effects of a combination of the soluble myostatin receptor ActRIIB (sActRIIB) and the b 2 -agonist formoterol in the cachectic Lewis lung carcinoma model. The combination of formoterol and sActRIIB was extremely effective in reversin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 44 publications
6
75
0
Order By: Relevance
“…In addition, gene expression analysis in tumor tissue showed this phenotype to be associated with reduced expression of genes involved in angiogenesis, tumor metabolism, activin signaling, and apoptosis. These results are consistent with studies showing that the soluble type II receptor antagonist of myostatin and activin (sActRIIB) reduced tumor weight and incidence of lung metastases (45, 53). Taken together, myostatin/activin signaling has a critical role not only in muscle cell degradation but also cancer progression, although it should be noted that these data have not been reproduced in other studies.…”
Section: Clinical-translational Advancessupporting
confidence: 91%
“…In addition, gene expression analysis in tumor tissue showed this phenotype to be associated with reduced expression of genes involved in angiogenesis, tumor metabolism, activin signaling, and apoptosis. These results are consistent with studies showing that the soluble type II receptor antagonist of myostatin and activin (sActRIIB) reduced tumor weight and incidence of lung metastases (45, 53). Taken together, myostatin/activin signaling has a critical role not only in muscle cell degradation but also cancer progression, although it should be noted that these data have not been reproduced in other studies.…”
Section: Clinical-translational Advancessupporting
confidence: 91%
“…Importantly, this treatment stimulated stem cell growth and prolonged animal survival. A recent study using the LLC cachexia model confirmed the beneficial effect of sActRIIB [71].…”
Section: Myostatin Inhibitormentioning
confidence: 72%
“…Mice were tested individually, multiple times until pulling away from the device horizontally resulted in both front paws grasping firmly and resisting to the point of pulling the force transducer measurably. Force was measured in grams (Toledo et al, 2016). …”
Section: Methodsmentioning
confidence: 99%